Adherence of the NTP to DOTS recommended defaulters tracing mechanism in Khyber Pakhtunkhwa, Pakistan (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Tuberculosis is still a major public health problem worldwide. Pakistan is one of the few countries with extremely high tuberculosis (TB) incidence and ranks sixth among the 22 high TB burden countries. World Health Organization (WHO) and International Union Against Tuberculosis and Lung Diseases (IUATLD) advocate the use of DOTS strategy to control tuberculosis. The study aimed to determine the adherence of DOTS facilitators and treatment supporters to the defaulter tracing mechanisms in Khyber Pakhtunkhwa. Methodology: A Cross Sectional study was conducted in fi ve districts Khyber Pakhtunkhwa. A total of 200 participants were included in the study of which 150 were DOTS facilitators and 50 were treatment supporters. A pre-tested structured questionnaire was administered to the participants. Five randomly districts of Khyber Pakhtunkhwa were selected out of the total of 24 districts and from each district 10 health facilities were then chosen. The DOTS facilitator and treatment supporters attached to these health facilities were interviewed. Two Focus Group Discussions were also held from a group of defaulted patients. Results: The study showed that 90% of the health facilities did not have desk guides and 82% of the treatment supporters did not receive training in DOTS strategy. The reasons of defaulting mentioned by DOTS defaulters in the Focus Group Discussion were lack of defaulter tracing mechanism that approach them and health education regarding the hazards of treatment interruption. Conclusion: The study is very signifi cant as it highlights the deficiencies in implementation of DOTS tracing mechanism. The findings of the study could be of help to national as well as provincial tuberculosis programme. The main recommendation is to provide training to treatment supporters in DOTS strategy and to update guidelines for defaulter tracing. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 1-7 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6958